2020
DOI: 10.1111/jan.14381
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of web‐based mobile health interventions in paediatric outpatient surgery: A systematic review and meta‐analysis of randomized controlled trials

Abstract: Aims To evaluate the effectiveness of web‐based mobile health interventions on paediatric patients and their parents in the day surgery context, where the primary outcome was children's pre‐operative anxiety and secondary outcomes were postoperative pain and parents’ anxiety and satisfaction with entire course of the day surgery. Design A systematic review and meta‐analysis of randomized controlled trials. Data Sources CENTRAL, CINAHL, Scopus, Ovid MEDLINE, and Web of Science were systematically searched witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 63 publications
3
44
0
Order By: Relevance
“…Moreover, the TPS group perceives higher social support and lower children's emotional and behavioural problems. Given that covid-19 post-lockdown months may have constituted a risk factor for Italian parents' health and may increase parental burnout in vulnerable families, these findings respond to the scientific debate over the positive effects of web-based interventions to support pediatric patients [12,13,14,15,16,17,18,45]. These data align with recent research demonstrating the association between parents' and children's wellbeing during covid-19 outbreak in Italy [1].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Moreover, the TPS group perceives higher social support and lower children's emotional and behavioural problems. Given that covid-19 post-lockdown months may have constituted a risk factor for Italian parents' health and may increase parental burnout in vulnerable families, these findings respond to the scientific debate over the positive effects of web-based interventions to support pediatric patients [12,13,14,15,16,17,18,45]. These data align with recent research demonstrating the association between parents' and children's wellbeing during covid-19 outbreak in Italy [1].…”
Section: Discussionsupporting
confidence: 82%
“…Covid-19 restrictions have led to adapt the Play Specialist approach for the online environment. In the light of a recent meta-analysis supporting the beneficial effects of a wide range of web-based health interventions in pediatric patients [45], this crisis has represented both a challenge and an opportunity to reshape the Play Specialist approach in the online environment. Specifically, the present study intends to verify whether and how a telematic adaptation of Play Specialist's intervention (TPS) beneficially impacts on families by focusing on variables defining parental wellbeing (i.e., parental burnout, anxiety, stress, depression, perceived social support).…”
Section: B Providing the Play Specialist Approach In The Era Of Coromentioning
confidence: 99%
“…In the study by Carlsson and Henningsson [ 47 ], the researchers realized that visiting the operation room might not reduce parents’ or children’s anxiety in surgery care situations. This finding is contradicted by the study of Rantala et al [ 18 ], who argued based on a recent meta-analysis that web-based interventions (eg, educational web-based programs or age-appropriate streamed videos) could be used to reduce children’s anxieties [ 18 ]. In another study by Rantala et al [ 23 ], health specialists observed that a digital gaming solution (developed for a hospital environment, including virtual visits to the hospital for different surgeries) would help families and children to be better oriented to an upcoming treatment.…”
Section: Discussionmentioning
confidence: 99%
“…According to the previous meta-analysis, digital gaming solutions can reduce children’s preoperative anxiety and increase parental satisfaction [ 18 ]. In addition, digital gaming solutions can be considered as nonpharmacological distraction tools for children.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation